(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: The study explored the perceived relevance of the Tanzania Institute of Accountancy programmes, examined the influence of these programmes on female graduates’ harnessing of blue economy opportunities, and determined the constraints against female graduates’ harnessing of blue economy opportunities. Design/Methodology/Approach: The study adopted a sequential exploratory mixed methods design. Data were collected through questionnaires from 345 female graduates sampled randomly from 2,267 female graduates of the Tanzania Institute of Accountancy in 2023/2024. The descriptive and inferential techniques were used for data analysis and presentation. Findings: The study found that the bachelor’s degree programmes offered by the Tanzania Institute of Accountancy are relevant to enhance female graduates’ harnessing of blue economy opportunities. Marketing and Public Relations, Procurement and Logistics Management, Business Administration and Bachelor of Accountancy have a positive association and significant influence on female graduates harnessing blue economy opportunities, unlike the Bachelor of Human Resource, which has insignificant influence. Research Limitation: The study disclosed the cause-effect relationship between business studies programs and harnessing blue economy opportunities in Tanzania, but did not investigate the sustainability of the blue economy resources or the productivity of these opportunities discussed and explained to the blue economy. Practical implication: The study calls for establishing a policy review to encourage practitioners to engage in the opportunities available in the blue economy to sustain economic growth. Social Implication: Female graduates’ involvement in sustainable coastal livelihoods, marine conservation, and ocean-based tourism can strengthen community resilience to environmental and economic challenges. Originality/value: The study described how having skills from business studies programmes does not guarantee a graduate’s ability to utilise blue economy resources due to personal, policy, socio-cultural, and economic barriers.